Model for Prevention of Hand, Foot and Mouth Disease in Child Care Center in the city of Patthalung and Trang Province - เชี่ยวชาญยนต์, บงกช; หนูฟอง, ปรีชา; เหมพัฒน์, สุนีย์ (Disease Control Journal, 2010)
The objective of this study was to develop a model for preventing of hand, food and mouth disease in child care center. The samples were purposively sampling from 36 child care centers which included 230 of staffs and 3,086 of children. The research was implemented during the year 2007 - 2008. The research procedure consisted of 3 parts, the first was training part, the second was pre-evaluation and post-evaluation part, the third was pre-interview and post- interview of the project stake holder. The result showed the score of development activity and environmental evaluation of the child care center was significantly difference between prescroe (x = 35.74+5.77) and post implemented (x = 43.67+4.87), This study revealed that child care staff had ability for screening and follow-up of suspected case. There were 18 cases within 3 months before project conducted compared to 11 cases after project implementation, The stake holder was satisfied with the usefulness and respond to their concern. In conclusion we demonstrated a feasible model for hand, foot and mouth screening in child care center and kindergarten school.